RISK COVERAGE FINES FOR MURABAHA FINANCING AT PT. FEDERAL INTERNATIONAL FINANCE BANDA ACEH BRANCH - Safira Mustaqilla; Miftahul Jannah; Shabarullah (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2019)
This article aims to examine the concept of fines on credit financing using the Murabahan contract at PT Federal International Finance Banda Aceh Branch, Indonesia. The research approach used is conceptual and legislative approach, the type of research used is normative juridical. The results showed that the basis for determining the penalty imposed by PT FIF based on fatwa NO.17/DSN-MUI/IX/2000 is because the debtor is able to make payments but delays payment, this aims to deter the debtor in default. Then from its practice in taking profits it does not use interest but PT FIF tells the amount of profit margin obtained by PT FIF as the financing party, the amount of margin in this case has certainly been agreed by both parties in the agreement, but the fine at PT FIF has been applied at the beginning of the contract which makes the fine haram because it does not meet the requirements of the scholars' opinions in Fiqh Muamalah that fines cannot be required at the beginning of the contract.